Improvement of quality analysis (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
Current study analyses the relationships between working capital management and profitability forKazakhstan firms. Previously no studies have been conducted on the same topic in Kazakhstan, andtherefore there is no available empirical evidence on the issue. The analyses are based on the OLS regressionand covariance analysis applied to the sample of 133 firms listed in Depositary of Financial Statements.The empirical results found the significant relationship between working capital managementand firms’ operating performance. Firms with better working capital management determined by shortercash conversion cycle were more profitable than those with longer cash conversion cycle. The resultsof the study indicate that owners and managers of firms can improve overall operating efficiency andprofitability by reducing cash conversion cycle to the reasonable minimum: avoid excessive inventorybalances, decrease receivables collection period, and defer payments to suppliers. The study contributesto the existing literature by examining the effect of working capital management on profitability in thecontext of the emerging market of Kazakhstan.